ADHM polytopes - James P. Allen; Paul Sutcliffe (Journal of High Energy Physics, 2013)
GLUT1-targeted therapy is a promising approach for treating various diseases. However, overcoming the poor competitiveness of glucose-analog ligands to bind glucose molecules is highly challenging. In this study, parishins isolated from Gastrodia elata are reported as high-affinity GLUT1 ligands(-9.859 kcal/mol for parishin A), identifying them as novel class of high-potential GLUT1 ligands. Using G. elata extract, parishin-modified selenium nanoparticles (P@Se NPs) in a green one-pot process were prepared. P@Se NPs perform uniform size and well-defined core-shell structure, where the Se NP core was coated with G. elata extract (hydrodynamic diameter: 92.73±0.40 nm; zeta potential: -24.30±0.55 mV). In a liver injury model, P@Se NPs shows enhanced GLUT1-mediated uptake (4.03-fold higher than that in free dye) and liver targeting (1.34-fold higher than that in free dye). P@Se NPs effectively alleviated hepatocyte necrosis induced by mitochondrial dysfunction and significantly improved key liver function indicators (AST, ALT, LDH, and T-Bil). Mechanistically, P@Se NPs restore mitochondrial function by normalizing oxidative stress (MDA, CAT, and SOD) and anti-inflammation (iNOS, IL-1β, and TNF-α), demonstrating effective GLUT1-targeting-assisted synergistic antioxidant and anti-inflammatory effects for hepatoprotection. This study provides a novel biomimetic GLUT1-targeted nanoplatform and offers a modern approach to developing traditional medicine components.